Training of Artificial Intelligence Applications for English Students - Syafryadin; Syahrial, Syahrial (Universitas Bengkulu, 2023)
This community service is motivated by students in Bengkulu who are considered by many to be untouched by the updated technology used in teaching English. Therefore, it is necessary to provide knowledge about learning technology through training. The purpose of this service activity is to train and realize habituation of English students at Fatmawati Sukarno State Islamic University (UIN FAS) Bengkulu so they are able to apply Artificial Intelligence applications in learning English. In carrying out this activity, the service method is carried out in the form of socialization and training and evaluation. This trial activity is related to UIN FAS. UIN FAS is an institution that has the same vision as the team implementing this community service activity, namely to educate the life of the Indonesian nation. Evaluation activities in community service are related to all things that occur in the process of implementing activities. This starts from the initial stage of preparation which includes field observations to training evaluation. The result of this dedication is that AI applications can be used by TBI UIN FAS students. They were very enthusiastic to take part in the training. In addition, they provide a good perception of the implementation of this AI training to support the English learning process.